1987
DOI: 10.1254/jjp.43.237
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cholinesterase in canine venous system.

Abstract: Abstract-Cholinesterase (ChE) activity was examined in 15 veins from dogs by pharmacological and histochemical procedures. Potentiation of acetylcholine (ACh)-induced contractile response by neostigmine was observed in helical and longitudinal strips of portal, mesenteric veins and middle segment of the inferior vena cava, but not in the other 12 veins. Histochemical studies with an electron microscope (the method of Karnovsky-Roots) revealed that ChE activity was identified as high density granules around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The preconstrictions evoked by me thoxamine slighly varied among the veins, but the regional difference in endothelium-depen dent relaxations were not related to the varia tion of the preconstriction levels (see, for in stance, the results of jugular vein and azygos veins in Table 1). Acetylcholine is known to cause the contractile responses in the veins showing the endothelium-dependent relaxa tions in the present study (6,9). However, the influence of such contractions on the observed relaxation responses seemed unlikely, because ACh-induced contractile responses of these veins occurred at higher concentration than 10-6 M (6, 9), whereas the endothelium dependent relaxations evoked by ACh were seen at lower concentrations than this, and maximum responses were obtained around 3x10-7 M. Thus, the present study indicated that the endothelium-dependent relaxation responses to ACh are regionally different in the canine venous system.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…The preconstrictions evoked by me thoxamine slighly varied among the veins, but the regional difference in endothelium-depen dent relaxations were not related to the varia tion of the preconstriction levels (see, for in stance, the results of jugular vein and azygos veins in Table 1). Acetylcholine is known to cause the contractile responses in the veins showing the endothelium-dependent relaxa tions in the present study (6,9). However, the influence of such contractions on the observed relaxation responses seemed unlikely, because ACh-induced contractile responses of these veins occurred at higher concentration than 10-6 M (6, 9), whereas the endothelium dependent relaxations evoked by ACh were seen at lower concentrations than this, and maximum responses were obtained around 3x10-7 M. Thus, the present study indicated that the endothelium-dependent relaxation responses to ACh are regionally different in the canine venous system.…”
mentioning
confidence: 64%
“…However, there are only a few reports de scribing the endothelium-dependent re sponses of veins (3,4). In previous papers, we repeatedly indicated that the canine venous system consists of veins characteristically different in pharmacological responses (5)(6)(7)(8)(9). Therefore, in the present study, distribution of endothelium-dependent relaxation re sponses in the venous system was inves tigated by using 15 canine veins selected systematically (5,6).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…These abdominal vessels stain positively for acetylcholinesterase, 130 and both longitudinal and circular muscle strips of these vessels contract to transmural field stimulation after combined a x -and a 2 -adrenergic receptor blockade. 126 " 128 This residual but substantial constriction is blocked by atropine and enhanced and prolonged by physostigmine and neostigmine.…”
Section: Veinsmentioning
confidence: 97%